Soft Skill Customer Care dan Literasi Bisnis Digital sebagai Prediktor Kesiapan Kerja - Nisa, Lidia Oktapiatun; Sartika, Sri Hardianti; Gumilar, Rendra (SJEE (Scientific Journals of Economic Education), 2026)
This study aims to determine the effect of customer care soft skills and digital business literacy on students' job readiness. This study uses a quantitative approach with a survey method and an explanatory research design to examine the causal relationship between variables. The population in this study were all 139 students of grade XI in Online Business and Marketing Expertise at SMK Negeri 1 Tasikmalaya in the 2025/2026 academic year. Data analysis was conducted using multiple linear regression analysis with the help of the SPSS program, and supported by analysis prerequisite tests including normality, linearity, multicollinearity, and heteroscedasticity tests. The results show that customer care soft skills have a positive and significant effect on students' job readiness. Digital business literacy also has a positive and significant effect on job readiness. Simultaneously, customer care soft skills and digital business literacy have a significant effect on students' job readiness. These findings confirm that strengthening soft skills and digital literacy are important factors in improving the job readiness of vocational high school students.